Preserved right ventricular function but increased right atrial contractile demand in altitude-induced pulmonary hypertension - Sareban, Mahdi; Perz, Tabea; Macholz, Franziska; Reich, Bernhard; Schmidt, Peter; Fried, Sebastian; Mairbäurl, Heimo; Berger, Marc Moritz; Niebauer, Josef (The international journal of cardiovascular imaging, 2020)
Purpose: Ascent to high altitude increases right ventricular (RV) afterload and decreases myocardial energy supply. This study evaluates physiologic variables and comprehensive echocardiographic indices of RV and right atrial (RA) function following rapid ascent to high altitude. Methods: Fifty healthy volunteers actively ascended from 1130 to 4559 m in < 22 h. All participants underwent 2D echocardiography during baseline examination at low altitude (424 m) and at three study time-points (7, 20 and 44 h) after arrival at high altitude. In addition to systolic pulmonary artery pressure (sPAP), comprehensive 2D planimetric-, tissue Doppler- and speckle-tracking-derived strain indices of RA and RV function were obtained. Results: sPAP increased from baseline (24 ± 4 mmHg) to the first altitude examination (39 ± 8 mmHg, p < 0.001) and remained elevated during the following 44 h. Global RV function did not change. RA reservoir strain showed a trend towards increase from baseline (50.2 ± 12.1%) to the first altitude examination (53.8 ± 11.0%, p = 0.07) secondary to a significant increase of RA contraction strain (19.2 ± 6.4 vs. 25.4 ± 9.6%, p < 0.001). Volumetric RA data largely paralleled RA strain results and RA active emptying volume was increased throughout the 44 h stay at high altitude. Conclusion: Active and rapid ascent of healthy individuals to 4559 m is associated with an increased contractile performance of the RA that compensates for the increased workload of the RV. Electronic supplementary material: The online version of this article (10.1007/s10554-020-01803-x) contains supplementary material, which is available to authorized users.